GIS BASED FLOOD HAZARD AND VULNERABILITY MAPPING: A CASE STUDY OF TIDAL AND RIVER FLOODS IN DOWNSTREAM OF CIASEM WATERSHED, SUBANG-WEST JAVA - Budi Hadi Narendra; Harris Herman Siringoringo; Chairil Anwar Siregar (Indonesian Journal of Forestry Research, 2017)
Flood events in downstream of  Ciasem watershed are believed to occur due to degradation of  watershed and mangrove cover. This paper studies the flood hazard and vulnerability caused by tidal and river flood, mainly on vegetation and built up areas as the main element of  risk. The observation was focused at downstream of  Ciasem watershed, located in MuaraVillage, Blanakan subdistrict, north coastal region of  Subang District. Tidal flood hazard was mapped using iteration process in ILWIS 3.4 software while river flood hazard map was made up incorporating elevation, slope and river characteristics using hydrological tools (HEC-geo RAS and HEC-RAS) in ArcGIS 10 software. Those hazard maps were then utilized to determine element of  risk covering vegetation and built up areas. Result showed that tidal inundation started to happen in the western area dominated by fish ponds as the main element of  risk.When sea level rose up to 90 cm height, settlement areas were experiencing inundation by tidal flood. Ciasem River began to over flowwhen the river discharge exceeded 160 m3/sec and inundated the paddy fields, fish ponds and settlements. This study indicated that fish ponds and paddy fields having high vulnerability to the flood event while that of  settlements and roads depend on the construction materials. Flood disaster risk should be reduced by continuing the land rehabilitation activity, restoring mangrove vegetation, implementing government regulations on management and establishment of  aquaculture in mangrove, and carefully considering  the construction of  coastal protection barriers.